Expert System to Predict the Type of Fever Using Data Mining Techniques on Medical Databases - Jagannatha Reddy, MV; Kavitha, B (International Journal of Computer Sciences and Engineering, 2025)
By finding the most important medical symptoms and laboratory data helps in building an expert system to predict the dengue fever in early stages. We developed in this project a new expert system to predict the dengue fever in early stages. This methodology consists of three important steps: a) manual missing value imputation method is applied that makes the data consistent. b) An expert doctors opinion is taken for selecting most influential attributes for dengue fever also we done internet survey . c) A neural network model is used for accurate prediction of dengue fever. The expert system is developed using MATLAB 2013. This methodology is seems to be giving good predictive results compared to other techniques.